The impact of short selling on stock prices, volatility, and liquidity: evidence from the Malaysian Intraday Short Selling (IDSS) framework of 2018 - Yau, Sue Meng (2019)
This paper examines the impacts of the intraday short selling (IDSS) framework on stock prices, volatility, and liquidity, by taking advantage of the unique settings of IDSS that requires the short positions to be closed on the same day before market closing. The paper supports the overvaluation hypothesis, where stock prices appear to be upwardly biased, especially small-cap stocks, when the retail investors are prohibited from short selling. The IDSS framework corrects the stock prices from being overvalued, improving the pricing efficiency. Moreover, the paper finds strong evidence that the removal of short selling restrictions for retail investors reduces the intraday returns volatility, especially for the small-cap stocks. The paper describes the lower volatility as a reflection of balanced demand and supply of stocks by virtue of IDSS framework. On the other hand, the paper finds that trading volume increases significantly when the short selling restrictions are removed for retail investors. The findings also show significantly increased in the opening and closing matches, which may due to opening or closing orders associated with fund flows.